Production of Liquid Fuel from Motorcycle Used Tire via Pyrolysis: Effect of Temperature on Yield and Calorific Value - Wulandary, Indah Retno; Octavia, Yona (Eksergi, 2025)
The continuous accumulation of used tires has raised serious environmental concerns due to their non-biodegradable nature. Pyrolysis offers a promising thermal conversion method to transform used tires into alternative energy sources. This study investigates the pyrolysis of used motorcycle tires, cut into 1 x 1 cm pieces, under atmospheric pressure at various temperatures ranging from 400°C to 750°C, using 500 grams of tire material for each run. The tar and char yields were collected, and the calorific values of the liquid product were analyzed. The optimum operating condition was found at 700°C, yielding 276.56 g of tar and 184.55 g of char after 2 hours and 35 minutes of reaction. The highest calorific value obtained was 39.98 MJ/kg. Although the liquid fuel produced exhibits significant energy content, its calorific value remains lower than that of conventional fuels used in vehicles. This indicates the potential of tire-derived oil as a supplementary fuel, with further improvement needed in quality and performance.